Design of Marine Facilities : Engineering for Port and Harbor Structures. - Gaythwaite, John W. (Reston : American Society of Civil Engineers, 2016)
Gaythwaite provides the essential reference for civil and structural engineers designing port and harbor structures for all types of marine facilities.
12.3 Element and Facility Condition Assessments -- 12.4 Documentation and Reporting -- 12.5 Lifecycle and Asset Management -- References -- Appendix 1: Conversion Factors -- Appendix 2: Selected Information Sources: Journals, Periodicals, and Conference Proceedings -- Appendix 3: Internet Sources and Selected Websites -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Harbors--Design and construction; Electronic books